Application of SCS Curve Number Model for Estimation of Runoff in Forest Micro-Watersheds of Shiwalik Region - A.K. Tiwari,; V.K. Bhatt, (Journal of Soil and Water Conservation, 2022)
The curve number procedure combining the hydrologic effect of soils, land use and treatment and antecedent moisture condition can be used conveniently for estimating the runoff from individual storms. The present study illustrates the calibration of curve number for the two forest hilly watersheds, WM-I and WM-2 of Shiwalik region in Chandigarh as a function of daily rainfall. The model was further validated with the segregated data of both the watersheds. On comparing the predicted and observed values Nash — Sutcliffe model efficiency was found to be 66 and 67 per cent with correlation coefficient of 0.86 and 0.89 for WM-I and WM-2,respectively. The results depict the suitability of model for estimating the water yield from small watersheds. The technique can be used for other similar watersheds where rainfall data is available.